Neutrophils Affect IL-33 Processing in Response to the Respiratory Allergen Alternaria alternata - Van Nevel, Sharon; van Ovost, Judith; Holtappels, Gabriele; De Ruyck, Natalie; Zhang, Nan; Braun, Harald; Maes, Tania; Bachert, Claus; Krysko, Olga (Frontiers in Immunology, 2021)
Future precision medicine requires further clarifying the mechanisms of inflammation in the severe endotypes of chronic airway diseases such as asthma and chronic rhinosinusitis (CRS). The presence of neutrophils in the airways is often associated with severe airway inflammation, while their precise contribution to the severe inflammation is largely unknown. We aimed to study the role of neutrophils in BALB/c and C57BL/6 mice exposed to Alternaria alternata (Alt). The mice were exposed to Alt extract for twelve hours or ten days to induce allergic airway inflammation. C57BL/6 mice exposed to Alt responded with eosinophilic infiltration and the characteristic IL-5 upregulation. In contrast, the inflammatory response to Alt extract in BALB/c mice was characterized by a neutrophilic response, high levels of G-CSF, and elastase in the lungs. The lack of neutrophils affected the processing of IL-33 in BALB/c mice, as was demonstrated by depletion of neutrophils through intraperitoneal injections of anti-Ly6G antibody. Our data identifies the key role of neutrophils in airway inflammation through IL-33 cleavage in the Alt-induced airway inflammation in mice, which could potentially underline the different endotypes in human disease.